Meniscal Treatment as a Predictor of Worse Articular Cartilage Damage on MRI at 2 Years After ACL Reconstruction: The MOON Nested Cohort. Issue 4 (March 2022) - Altahawi, Faysal F.; Reinke, Emily K.; Briskin, Isaac; Cantrell, William A.; Flanigan, David C.; Fleming, Braden C.; Huston, Laura J.; Li, Xiaojuan; Oak, Sameer R.; Obuchowski, Nancy A.; Scaramuzza, Erica A.; et al.
Background: Patients undergoing anterior cruciate ligament reconstruction (ACLR) are at an increased risk for posttraumatic osteoarthritis (PTOA). While we have previously shown that meniscal treatment with ACLR predicts more radiographic PTOA at 2 to 3 years postoperatively, there are a limited number of similar studies that have assessed cartilage directly with magnetic resonance imaging (MRI). Hypothesis: Meniscal repair or partial meniscectomy at the time of ACLR independently predicts more articular cartilage damage on 2- to 3-year postoperative MRI compared with a healthy meniscus or a stable untreated tear. Study Design: Cohort study; Level of evidence, 2. Methods: A consecutive series of patients undergoing ACLR from 1 site within the prospective, nested Multicenter Orthopaedic Outcomes Network (MOON) cohort underwent bilateral knee MRI at 2 to 3 years postoperatively. Patients were aged <36 years without previous knee injuries, were injured while playing sports, and had no history of concomitant ligament surgery or contralateral knee surgery. MRI scans were graded by a board-certified musculoskeletal radiologist using the modified MRI Osteoarthritis Knee Score (MOAKS). A proportional odds logistic regression model was built to predict a MOAKS-based cartilage damage score (CDS) relative to the contralateral control knee for each compartment as well as for the whole knee, pooled by meniscal treatment, while controlling for sex, age, body mass index, baseline Marx activity score, and baseline operative cartilage grade. For analysis, meniscal injuries surgically treated with partial meniscectomy or meniscal repair were grouped together. Results: The cohort included 60 patients (32 female; median age, 18.7 years). Concomitant meniscal treatment at the time of index ACLR was performed in 17 medial menisci (13 meniscal repair and 4 partial meniscectomy) and 27 lateral menisci (3 meniscal repair and 24 partial meniscectomy). Articular cartilage damage was worse in the ipsilateral reconstructed knee ( P < .001). A meniscal injury requiring surgical treatment with ACLR predicted a worse CDS for medial meniscal treatment (medial compartment CDS: P = .005; whole joint CDS: P < .001) and lateral meniscal treatment (lateral compartment CDS: P = .038; whole joint CDS: P = .863). Other predictors of a worse relative CDS included age for the medial compartment ( P < .001), surgically observed articular cartilage damage for the patellofemoral compartment ( P = .048), and body mass index ( P = .007) and age ( P = .020) for the whole joint. Conclusion: A meniscal injury requiring surgical treatment with partial meniscectomy or meniscal repair at the time of ACLR predicted worse articular cartilage damage on MRI at 2 to 3 years after surgery. Further research is required to differentiate between the effects of partial meniscectomy and meniscal repair.